Factor IX-Padua enhances the fibrinolytic resistance of plasma clots - Ammollo, Concetta T.; Semeraro, Fabrizio; Colucci, Mario; Simioni, Paolo (Thrombosis and Haemostasis, 2014)
Hypercoagulable conditions may determine a hypofibrinolytic state by increasing the activation of thrombin-activatable fibrinolysis inhibitor (TAFI). Factor (F)IX-Padua is a mutated FIX with an eight-fold increased clotting activity and associates with a higher venous thrombotic risk. We evaluated the influence of FIX-Padua on TAFI-mediated regulation of fibrinolysis. A subject hemizygous for FIX-Padua, two family members (heterozygous and normal) and six healthy controls were studied. Clot lysis, TAFI activation and thrombin generation were evaluated in contact-inhibited plasma challenged with low concentrations of tissue factor. Fibrinolysis times were significantly longer in FIX-Padua carriers than controls. The difference disappeared when activated TAFI (TAFIa) was inhibited, when TAFI activation was avoided or when clotting was made independent of FIX. TAFIa generation was markedly enhanced in FIX-Padua carriers as compared to controls, and this could be explained by a greater thrombin generation in the former. Hyperactive FIX, but not wild-type FIX, enhanced fibrinolytic resistance also when the FXI-dependent positive feedback was blocked by a neutralising anti-FXI antibody. This thrombin-mediated, TAFI-dependent down-regulation of fibrinolysis provides new clues for explaining the heightened thrombotic risk in subjects carrying the FIXPadua mutation.
Keywords: Factor IX; fibrinolysis; thrombin activatable fibrinolysis inhibitor; thrombin generation; thrombosis